Probing the Structure of Liquids with 129Xe NMR Spectroscopy: n-Alkanes, Cycloalkanes, and Branched Alkanes - Morgado, Pedro (2013)
The liquid organization of linear, branched, and cyclic alkanes was studied using atomic 129Xe as a NMR probe. 129Xe chemical shifts have been experimentally determined for xenon dissolved in a total of 21 alkanes. In order to allow the comparison of the different solvents at similar thermodynamic conditions, the measurements were performed over a wide range of temperatures, from the melting point of the solvent up to 350 K. The results were rationalized in terms of the density, nature, and organization of the chemical groups within xenon’s coordination sphere. Additionally, molecular dynamics simulations were performed using established atomistic force fields to interpret and clarify the conclusions suggested by the experimental results. The analysis is able to interpret previous results in the literature for ethane and propane at very different experimental conditions.